Supply Chain Management in the Era of Industrial Revolution 4.0 in MSMEs - Thokozani Jere Thokozani; Izelda Mucavele Mucavele; Armando Mabunda Mabunda (ICON Publisher, 2025)
The advent of the Fourth Industrial Revolution (IR 4.0) has significantly transformed supply chain management (SCM), particularly within Micro, Small, and Medium Enterprises (MSMEs). This literature review aims to synthesize recent research on the integration of IR 4.0 technologies in SCM for MSMEs, highlighting both opportunities and challenges. By examining peer-reviewed journal articles indexed in Scopus, this review provides a comprehensive overview of the current state of knowledge, identifies research gaps, and suggests future research directions. The integration of Industry 4.0 (IR 4.0) technologies into supply chain management (SCM) offers transformative potential for micro, small, and medium-sized enterprises (MSMEs), enhancing efficiency, reducing costs, and improving transparency. This literature review examines the adoption of key IR 4.0 technologies—such as IoT, big data analytics, AI, and blockchain within MSME supply chains, highlighting the opportunities and challenges encountered. Successful case studies from diverse sectors illustrate the practical benefits and strategies for overcoming adoption barriers. Despite the advantages, MSMEs face unique challenges, including financial constraints, lack of technical expertise, and cybersecurity risks. Future research should focus on scalable, cost-effective solutions tailored to MSMEs, addressing technological and human factors, and developing robust cybersecurity measures. Additionally, exploring supportive government policies and sustainable business models integrating IR 4.0 technologies is crucial. This review provides a comprehensive understanding of the current landscape and offers directions for future research, aiming to facilitate the digital transformation of MSMEs and enhance their competitiveness and sustainability in the global market.